Fatigue resistance of post-buckled slender trapezoidal corrugated webs in girders with stiff flanges. (1st November 2019) - Wang, Zhi-Yu; Yuan, Fang; Chen, Yang; Wang, Qingyuan; Chen, Tao; Zhou, Xiafang; Liu, Zifeng
Highlights: Fatigue behaviour of slender trapezoidal profiled web is experimentally tested. Two typical crack manners and post-buckling out-of-plane deflection are examined. Analytical models for shear resistances versus slenderness ratios are evaluated. Life prediction allowing for tension field and geometric features is justified. Abstract: Slender trapezoidal corrugated web does generally possess notable post-buckling capacity with certain reserve of shear resistance. Repeated secondary bending stresses due to post-buckling at the boundaries of the subpanel of the trapezoidal corrugated web, however, may result in potential local fatigue failure. A series of fatigue experimental tests on the slender profiled web girders with stiff flanges subjected to the action of predominant shear is outlined. The fatigue test results are presented in terms of stiffness deterioration and fatigue failure induced by out-of-plane deflection as the applied load exceeds the elastic critical load. It was found that fatigue cracks due to predominant shear action propagate much faster than these due to combined shear and tearing. Recommendations are prescribed for evaluating the fatigue resistance of post-buckled slender trapezoidal corrugated webs with appropriate detail categories codified in the Eurocode 3. Previously published analytical models correlating normalized shear resistances with relative plate slenderness ratios are compared against test data and discussed for their applicability. Based on the test results, a new mathematical representation is derived based on von Kármán's effective width concept for ultimate loads. The derived formula is demonstrated to correlate well with test data since reasonable allowances are given for the tension field theory and geometric characteristics of the trapezoidal corrugated webs.